2021
DOI: 10.3390/jcm10215125
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children with Down Syndrome: Data from the Trisomy 21 Research Society Survey

Abstract: Adults with Down Syndrome (DS) are at higher risk for severe outcomes of coronavirus disease 2019 (COVID-19) than the general population, but evidence is required to understand the risks for children with DS, which is necessary to inform COVID-19 shielding advice and vaccination priorities. We aimed to determine the epidemiological and clinical characteristics of COVID-19 in children with DS. Using data from an international survey obtained from a range of countries and control data from the United States, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
2
28
3
Order By: Relevance
“…Worries around health have been found to be increased in SEND families and our study seems to provide further support to such claims (Asbury et al, 2021 ). As highlighted by Emes et al, ( 2021 ), individuals with DS are at greater risk for severe outcomes of COVID-19, nonetheless our data suggest that this is not a major concern for families and individuals with DS.…”
Section: Discussionsupporting
confidence: 63%
“…Worries around health have been found to be increased in SEND families and our study seems to provide further support to such claims (Asbury et al, 2021 ). As highlighted by Emes et al, ( 2021 ), individuals with DS are at greater risk for severe outcomes of COVID-19, nonetheless our data suggest that this is not a major concern for families and individuals with DS.…”
Section: Discussionsupporting
confidence: 63%
“…Significant risk factors for their hospitalisation were older age, obesity, and epilepsy, and they were generally more prone to severe clinical presentation. Mortality rates were low in all paediatric COVID-19 patients, contrasting with previous findings in adults with Down syndrome who had higher mortality [ 131 ]. Among parents of children with an autism spectrum disorder in Southern California, approximately 35% intended to vaccinate their child [ 132 ]…”
Section: Study Of Covid-19 In Particularly Vulnerable Childrencontrasting
confidence: 80%
“…Some authors suggested that vaccines should be considered for implementation at child and adolescent psychiatric hospitals [ 128 ]. Others critically reviewed pre-and post-marketing evidence on the potential benefits and risks of marketed COVID-19 vaccines in special cohorts that included immunocompromised children, those with predispositions to allergies, children with other comorbidities [ 129 , 130 ], and those with Down syndrome [ 131 ]. It was shown that hospitalised minors with Down syndrome had a higher incidence of respiratory symptoms, fever, and several medical complications from COVID-19 than control patients [ 131 ].…”
Section: Study Of Covid-19 In Particularly Vulnerable Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Worries around health have been found to be increased in SEND families and our study seems to provide further support to such claims (Asbury et al, 2021). As highlighted by Emes et al, (2021), individuals with DS are at greater risk for severe outcomes of COVID-19, nonetheless our data suggest that it is not a major concern for families and individuals with DS.…”
Section: Worriesmentioning
confidence: 57%